Pitanga and grumixama extracts: antioxidant and antimicrobial activities and incorporation into cellulosic films against Staphylococcus aureus (Research, Society and Development, 2020)
There is great interest in developing alternatives to improve food safety, since food-borne diseases (FBD) are a major public health concern worldwide. Plant extracts have the potential to inhibit microbial growth due to the action of secondary metabolites, such as phenolic compounds. This study evaluated the antioxidant and antimicrobial activities of phenolic compounds extracted from grumixama (Eugenia brasiliensis) and pitanga (Eugenia uniflora) fruits and the antimicrobial potential of extract of grumixama upon incorporation into cellulosic films. Both fruits were rich in total phenolic compounds and their extracts showed antioxidant activity. The crude and phenolic extracts of grumixama showed higher activity than those isolated from pitanga. All extracts inhibited the growth of Staphylococcus aureus. After incorporation into cellulosic films, the crude extract of grumixama remained active, reducing the S. aureus population in 4 log cycles. The cellulosic films incorporated with grumixama extract were stable after seven days of storage under refrigeration at 7º C; but they partially lost antimicrobial activity when exposed to UV radiation. These phenolic compound-containing cellulosic films could be used as a complementary preservation method of foods that are prone to contamination with S. aureus.